(untitled) (Eurasian Scientific Herald, 2024)
In this article. The view of the word as a system that summarizes the oerseptions of reality in the sense of the unity of all its somponents, has been applied to various directions and fronts, and a reaction to the researches conducted in this regard has been expessed. For the furst time in Uzbek linguistics, attention was paid to the consept of artistic linguistic landscape of the world.